Local Drug Delivery for the Treatment of Neurotology Disorders - Piu, Fabrice; Bishop, Kathie M. (Frontiers in Cellular Neuroscience, 2019)
Neurotology disorders such as vertigo, tinnitus, and hearing loss affect a significant proportion of the population (estimated 39 million in the US with moderate to severe symptoms). Yet no pharmacological treatments have been developed, in part due to limitations in effective drug delivery to the anatomically protected inner ear compartment. Intratympanic delivery, a minimally invasive injection performed in the office setting, offers a potential direct route of administration. Currently, off-label use of therapeutics approved to treat disorders via systemic administration are being injected intratympanically, mostly in the form of aqueous solutions, but provide variable levels of drug exposure for a limited time requiring repeated injections. Hence, current drug delivery approaches for neurotology disorders are sub-optimal. This review, following a description of pharmacokinetic considerations of the inner ear, explores the merits of novel delivery approaches towards the treatment of neurotology disorders. Approaches employing local delivery to the inner ear are described, including direct intracochlear delivery as well as intratympanic methods of infusion and injection. Intratympanic injection delivery formulation strategies including hydrogels, polymers and nanoparticulate systems are explored. These approaches represent progress towards more effective delivery options for the clinical treatment of a variety of neurotology disorders.